(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
According to the Commission on Higher Education, 517,000 new college graduates enter the workforce each year. This statistic is taken from the Project Jobs Fit study conducted by the Department of Labor and Employment (DOLE) in 2009, which identified five industries as major sources of job openings or sources of employment: cyber services, hotels and restaurants, construction, health and wellness, aviation, and other hospitality-related industries. Among the most difficult-to-fill positions are those in these industries, which include "to open positions for which a business has had trouble filling them because there weren't any candidates, or because they didn't have the required training, knowledge, or credentials, other factors, such as a preference for working abroad, a desire for a greater wage, or a geographical issue. The research findings made it evident that a variety of factors, including projects, recitations, on-the-job training, and legal issues in the field, had an impact on alumni BSOA students' ability to locate employment opportunities. The survey results show that the majority of the alumni BSOA students had difficulties performing academically in terms of doing projects and recipes. Researchers advise BSOA alumni students to participate in a variety of programs on Tesda. We also advised them to take advantage of any available opportunities, such as work experience, in order to develop the knowledge and skills needed to secure employment in the legal sector.